Teoria della nascita e ricerche sull’inconscio - De Simone, Gianfranco (Il sogno della farfalla, 2019)
The aim of this article is to examine the new idea of unconscious, defined as mind without consciousness according to the Human Birth Theory by Massimo Fagioli. This new idea of the unconscious mind represents an original and organic model for both normal and pathological development. It also affirms the presence of a First Nuclear Self – as ability to imagine and memory of the sensation had – since birth. This new conception marks the end of the traditional idea supported by dynamic and psychoanalytic psychology, according to which biological and psychological birth would not correspond. The author proposes a methodological and theoretical comparison with different conceptions of unconscious in the psychoanalytic, cognitivist and neuroscientific field. Due to its structural, relational and evolutionary theoretical framework, the Human Birth Theory may represent a fundamental benchmark for all those disciplines investigating human mental reality. At the same time, it may provide the foundation for research on the unconscious dimension and ultimately a new perspective for the psychotherapeutic practice.